Exploring home advantage and quality of opposition interactions in the Chinese Football Super League - Liu, T.; Garcia-De-Alcaraz, A.; Zhang, L.; Zhang, Y. (International Journal of Performance Analysis in Sport, 2019)
The purpose of this study was to explore the influence of quality of opposition and match location on game-related statistics in the Chinese Football Super League (CSL). Seven hundred and twenty matches from season 2014 to 2016 of CSL were analysed and all teams were classified into two groups according to their final rankings at the end of each season. The game-related statistics were divided into goal scored, offensive, defensive, and physical variables. Mann-Whitney U-test with effect size at 95% of confidence interval, and Discriminant analyses were used. Results showed a home advantage (HA) near 60%. In addition, home teams showed significantly higher average values in performance indicators regardless of the team`s quality, especially in goal (score: 1.55 vs. 1.22; ES = 0.27 ± 0.10, and shots: 13.29 vs. 11.01; ES = 0.47 ± 0.10) and offence variables (possession: 0.51 vs. 0.49; ES = 0.33 ± 0.10). According to quality of opposition, superior teams played better at home in attacking categories like goal scored (1.83 vs. 1.39; ES = 0.34 ± 0.15) and offensive (possession: 0.53 vs. 0.51; ES = 0.33 ± 0.14). In conclusion, superior and inferior teams experience HA differently. These findings can help coaches to manage their team`s performance according to the contextual variables that influence on performance, especially about match location and quality of opposition.